Improvement of Spatial and Non-verbal General Reasoning Abilities in Female Veterinary Medical Students Over the First 64 Weeks of an Integrated Curriculum - Gutierrez, Juan Claudio; Holladay, Steven D.; Arzi, Boaz; Clarkson, Christina; Larsen, Roxanne; Srivastava, Sakti (Frontiers in Veterinary Science, 2019)
Spatial visualization ability is defined as the ability to mentally rotate 2- and 3-dimensional figures. Visual reasoning is the ability to manipulate mental images of an object to reach a certain conclusion, and has been linked to spatial ability. There is currently limited information about how entry-level spatial and visual reasoning abilities may be enhanced with progression through the rigorous veterinary medical curriculum. The present study made use of two tests that measure spatial ability, and one test that measures non-verbal general reasoning ability in female veterinary students: Guay's visualization of views test, adapted version (VVT); Mental Rotations Test (MRT); and Raven's Advanced Progressive Matrices Test, short form (APMT). Tests were given immediately before commencing the integrated veterinary medical curriculum (T0), at week 32 (T1) and, at week 64 (T2) into the program. Results showed improved spatial visualization ability as measured by VVT and MRT, and improved non-verbal general reasoning ability as measured by APMT, at both 32 and 64 weeks. The spatial ability scores measured by VVT and MRT showed a positive correlation with non-verbal general reasoning ability scores (APMT), supporting the idea that these abilities are linked.